Problematika impor sampah di Indonesia: Kepentingan politik, ekonomi, atau lingkungan? - Diah Fitri Ekarini; Nova Amalia Sakina; Mia Erpinda; Heri Prasetyo (Environment Conflict, 2024)
The waste issue in Indonesia remains an unresolved environmental concern, exacerbated by the problem of waste importation from developed countries to Indonesia, a practice that has been ongoing since 1989 until now. Since 2018, China, as the world's largest importer of waste, ceased its waste import activities with the implementation of the National Sword Policy (reducing drastically from 60% to 10%). This had repercussions on Indonesia, a developing country and a recipient of waste imports in Southeast Asia. The increase in the volume of waste imports from developed countries to Indonesia was approximately 320,000 tons in 2018. This article aims to discuss the issues of waste importation in Indonesia from political-ecological, social, and economic perspectives, as well as its environmental impact. The article also reviews the compliance with existing laws regarding the waste import mechanism in Indonesia. The literature review method is employed to compile this article, utilizing various research materials related to waste imports and policies in Indonesia. Based on the findings, it can be concluded that the waste import issue in Indonesia is a manifestation of political-ecological concerns, where environmental problems are greatly influenced by political (ego-sectoral) and economic aspects. The environmental interests mandated by the Basel Convention, which are subsequently translated into policies and regulations in Indonesia, have not been able to achieve their main objectives, namely, the protection of environmental and human health from the impacts of imported waste. The waste import policy in Indonesia needs to be reevaluated concerning the clarity of requirements and effective law enforcement when violations occur.